2019
DOI: 10.1186/s12889-018-6322-8
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic correlates of depressive symptoms: a cross-sectional analytic study among healthy urban Ghanaian women

Abstract: BackgroundStudies on healthy individuals that show minor signs of distress and depression—but that are not significant enough to be debilitating or to report to the hospital for treatment—are rare. Our primary objective was to measure the prevalence of depressive symptoms and sociodemographic correlates among healthy women 18 years and above in urban Accra, Ghana.MethodWe used secondary data from the Women’s Health Study of Accra, Wave 1 (WHSA-1), a large scale, analytic, cross-sectional study conducted in Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…Economically inactive employment status was associated with any mental disorder, any mood disorder, suicidality and any psychotic disorder. A strong association between depressive disorders and economically inactive status has also been found in many other studies [39,52].…”
Section: Factors Associated With a Current Mental Disordersupporting
confidence: 77%
“…Economically inactive employment status was associated with any mental disorder, any mood disorder, suicidality and any psychotic disorder. A strong association between depressive disorders and economically inactive status has also been found in many other studies [39,52].…”
Section: Factors Associated With a Current Mental Disordersupporting
confidence: 77%
“…In line with previous studies, our results demonstrated that unemployment increases the chance of anxiety and depression [20,29,30]. Economically, unemployment status increases the risk of development and progression of psychiatric disorders and strong evidence is available in this regard for depression and anxiety disorders [31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, our results demonstrated that unemployment increases the chance of anxiety and depression [19,28,29]. Economically, unemployment status increases the risk of development and progression of psychiatric disorders and strong evidence is available in this regard for depression and anxiety disorders [30][31][32].…”
Section: Discussionsupporting
confidence: 92%